Entrepreneurship Education and Family Environment as Determinants of Entrepreneurial Interest among Vocational Students in Garut District - Novian, Muhamad Ilham; Hamdani, Nizar Alam; lindayani, Lindayani (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This research examines the relationship between entrepreneurship education and family environmental factors on their interest in starting an entrepreneur. Entrepreneurship education is an important part in terms of how the family environment and education influence students' future, especially in relation to entrepreneurship. This research examines three variables, namely entrepreneurial interest, education, and family environment. The research subjects were graduates of SMK Negeri 2 Garut in 2019. Quantitative methods based on non-experimental or survey designs were used in this research. Using SPSS 26 statistics and simple purposive sampling procedures, 87 participants were selected for this study from a pool of Google Form responses. Based on the results of this study, entrepreneurship education is an important predictor of interest in entrepreneurship, with a positive effect size of 33%. There is a positive and statistically significant relationship of 21.7% between family environment variables and entrepreneurial interest. The variables entrepreneurship education and family environment have a positive and statistically significant relationship of 35% with interest in entrepreneurship. Other variables not included in this analysis are 65%.